Optimization of Community Entrepreneurship through Diversification and Digitalization of Locally Based Chocolate Beverages - Mulyati, Mulyati; Zebua, Selamat; Apriani, Desy; Oganda, Fitra Putri; Fitriani, Anandha; Sihotang, Sondang Visiana; Nesti Anggraini Santoso (ADI Journal on Recent Innovation, 2025)
Community-based entrepreneurship plays a vital role in strengthening local economies, particularly in the food and beverage sector where unique and innovative products are highly valued. Among these, locally based chocolate beverages present a promising opportunity for business growth. This study aims to examine how product diversification, digitalization, and consumer behavior influence the performance of entrepreneurs in the local chocolate beverage industry. A quantitative research approach was employed, with data collected through a structured survey involving 150 entrepreneurs and consumers directly engaged in the sector. The collected data were analyzed using statistical methods to evaluate the relationships between the three independent variables product diversification, digitalization, and consumer behavior and entrepreneurship performance as the dependent variable. The results demonstrate that all three factors have a significant and positive effect on entrepreneurship performance. Specifically, businesses that adopt product diversification strategies are better able to reach new consumer segments, reduce business risks, and strengthen brand identity. Meanwhile, the integration of digital technologies enhances market visibility, customer engagement, and operational efficiency. Consumer behavior further acts as a determinant of purchasing patterns, preferences, and loyalty, which in turn shape business strategies. The findings highlight that entrepreneurs who actively embrace diversification, digitalization, and consumer oriented approaches are more likely to achieve sustainable growth and competitive advantage. This research contributes to the academic discourse on entrepreneurship and provides practical insights for entrepreneurs, policymakers, and stakeholders in developing resilient community-based enterprises.